1979
DOI: 10.1179/bjo.6.3.145
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Timing of the Adolescent Growth Spurt from Ossification Events in Hand—Wrist Films

Abstract: The prediction of the timing of the pubertal growth spurt could be helpful in planning some types of orthodontic treatment. It has been suggested that information from hand—wrist radiographs could be used for this purpose. Insufficient attention has been paid to the distinction between ossification events and bone stages. In the present paper it is shown that the uncertainty of prediction of the timing of the peak height Velocity from ossification events in the hand and wrist, is generally large and so they ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
3

Year Published

1986
1986
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 8 publications
0
42
0
3
Order By: Relevance
“…As stated by Houston et al, 4 the use of individual ossification events is of limited use during pubertal growth-spurt prediction, and analysis that includes bone stages as well as ossification events is recommended. 3 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As stated by Houston et al, 4 the use of individual ossification events is of limited use during pubertal growth-spurt prediction, and analysis that includes bone stages as well as ossification events is recommended. 3 …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the hand-wrist radiograph is considered to be the most standardized method of skeletal assessment. 4,7,18,27 Although some studies 4,12,13 stated that the use of hand-wrist radiographs to predict growth spurt is not sufficiently accurate to be of value in clinical orthodontics, the validity of skeletal maturity assessment using the hand-wrist radiographs has been observed. 2,3 However, to avoid taking additional radiographs, it is relevant to relate maturational stages to skeletal features other than the bones in the hand and wrist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cervical vertebral bone age = −0.20 + 6.20 × AH 3 /AP 3 + 5.90 × AH 4 /AP 4 + 4.74 × AH 4 /PH 4 After calculating the skeletal maturity by both the methods the correlation and difference between cervical vertebral bone age and bone age by hand-wrist method were determined, as were those between cervical vertebral bone age and chronological age. …”
Section: Methodsmentioning
confidence: 99%
“…For many years, wrist radiography has been used to determine skeletal maturation. (6)(7)(8)(9) However, today researchers have concluded that radiography of cervical vertebrae is a good alternative to wrist radiography. Thus, cervical vertebrae maturation is a good diagnostic tool for estimating the pubertal growth spurt.…”
mentioning
confidence: 99%